2014
DOI: 10.1097/rhu.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Older Age at Rheumatoid Arthritis Onset and Comorbidities Correlate With Less Health Assessment Questionnaire–Disability Index and Clinical Disease Activity Index Response to Etanercept in the RADIUS 2 Registry

Abstract: Background Controversy exists in understanding the effects of age of onset and comorbidities in predicting rheumatoid arthritis (RA) response to biologic therapy. Objective To investigate the influence of age of onset and number of comorbidities on Health Assessment Questionnaire-Disability Index (HAQ-DI) and Clinical Disease Activity Index (CDAI) responses in active RA patients after 6 months of treatment with etanercept. Methods 1899 RA patients were assessed after 6 months of etanercept therapy. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
2
5
0
2
Order By: Relevance
“…10,11 Another perspective of analysis in this field is the possible impact of comorbidities on clinical response in patients with RA, PsA and SpA under treatment with biological drugs. 12,13 This approach has been widely used to assess the influence of a single comorbid disease, like obesity. 14 However, in the settings of real-life patients may often suffer from more comorbid conditions, and this raises the need of a whole assessment of comorbidities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Another perspective of analysis in this field is the possible impact of comorbidities on clinical response in patients with RA, PsA and SpA under treatment with biological drugs. 12,13 This approach has been widely used to assess the influence of a single comorbid disease, like obesity. 14 However, in the settings of real-life patients may often suffer from more comorbid conditions, and this raises the need of a whole assessment of comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the relationships between rheumatic diseases and comorbidities has further increased since the arrival onto the market of biological drugs with the concern that the selective blocking of tumour necrosis factor (TNF) or interleukin‐6 (IL‐6) may deteriorate the cardiac output or alter the lipid metabolism ensuing in a higher cardiovascular risk . Another perspective of analysis in this field is the possible impact of comorbidities on clinical response in patients with RA, PsA and SpA under treatment with biological drugs . This approach has been widely used to assess the influence of a single comorbid disease, like obesity .…”
Section: Introductionmentioning
confidence: 99%
“…Monti S et al (13) revealed that age and comorbidities in uence the choice towards ABA and TCZ compared to TNFi. Previous studies indicated that age and the presence of comorbidities are associated with a decreased response by Etanercept (19,20). Frisell T et al (7) reported that patients receiving TNFi were younger than the non-TNFi group.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, comorbidity was an independent risk factor for uncontrolled disease activity in the whole study population. Comorbidity was previously known to have an independent association with clinical measures, such as the CDAI and the Health Assessment Questionnaire [ 23 , 24 ]. We also found that the presence of comorbid disease has a significant correlation with disease activity indices, including DAS28.…”
Section: Discussionmentioning
confidence: 99%